2007
DOI: 10.1038/sj.onc.1210559
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic identification of ADAMTS18 as a novel 16q23.1 tumor suppressor frequently silenced in esophageal, nasopharyngeal and multiple other carcinomas

Abstract: Tumor Suppressor genes (TSGs) often locate at chromosomal regions with frequent deletions in tumors. Loss of 16q23 occurs frequently in multiple tumors, indicating the presence of critical TSGs at this locus, such as the well-studied WWOX. Herein we found that ADAMTS18, located next to WWOX, was significantly downregulated in multiple carcinoma cell lines. No deletion of ADAMTS18 was detected with multiplex differential DNA-PCR or high resolution 1-Mb array-based CGH analysis. Instead, methylation of the ADAMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
119
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 34 publications
11
119
1
Order By: Relevance
“…However, this concept is challenged by recent findings of several members showing to possess tumor suppressive functions (2)(3)(4)(5)(6). A disintegrins and metalloproteinases with thrombospondin motifs (ADAMTS), a family of extracellular metalloproteases, is structurally and functionally similar to matrix metalloproteinases (MMP) and ADAMs (7).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, this concept is challenged by recent findings of several members showing to possess tumor suppressive functions (2)(3)(4)(5)(6). A disintegrins and metalloproteinases with thrombospondin motifs (ADAMTS), a family of extracellular metalloproteases, is structurally and functionally similar to matrix metalloproteinases (MMP) and ADAMs (7).…”
Section: Introductionmentioning
confidence: 92%
“…Clonogenicity was determined by measuring colonies growing in monolayer culture as described previously (6,21). HONE1 and KYSE150 cells (1 Â 10 5 per well) were seeded in a 12-well plate and were transiently transfected with pcDNA3.1(þ)-ADAMTS8-Flag plasmid or the pcDNA3.1 vector alone, using FuGENE 6 (Roche).…”
Section: Colony Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Porter et al (14) demonstrated that there was a downregulation of several members of the ADAMTS family, including ADAMTS18, in human breast cancer compared with non-neoplastic mammary tissues. In addition, silencing of ADAMTS18 by methylation of promoter CpG islands has been reported in multiple carcinoma cell lines, particularly in cell lines derived from esophageal and nasopharyngeal carcinomas (15).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is now well established that alternative epigenetic silencing, such as methylation of promoter CpG islands (CGIs), leads to the inactivation of TSGs in virtually all tumour types and plays significant roles in tumour initiation and progression (Jones and Baylin, 2002). In CRC, epigenetic silencing of multiple TSGs has been reported frequently, including MLH1, p16 INK4A , MGMT, VHL, APC, RASSF1A, HIC1, CHFR, ADAMTS18 and PCDH10 in various percentages of CRC tumours (Herman et al, 1998;Esteller et al, 2001;Kim et al, 2005;Ying et al, 2006;Jin et al, 2007 ). A growing list of TSGs with CGI methylation-mediated silencing has also been reported in gastric cancer (Leung et al, 2001).…”
mentioning
confidence: 99%